It’s All About Food: The Contribution of Food Production and Consumption to Western Australia’s Lower Blackwood Region - Rooney, Angela Mary (Curtin University, 2024)
This thesis examines the food system in the Lower Blackwood catchment area in Western Australia’s southwest to analyse the historical contribution of food production and consumption and reflect on future opportunities. It is a creative PhD combining an exegesis and ArcGIS StoryMaps that uses transition theory to offer insight into local food production, consumption, local cooking and cuisines as a function of the changing socio-economic landscape, including climate change, food security, resilience and economic circumstances.